Outsourcing and public service values: the Australian experience - Mulgan, Richard (2005)
With the increasing use of private organizations to provide public services and the corresponding blurring of boundaries between the public and private sectors, can public servants be held to a distinct code of ethics or should public sector ethical standards be applied to private providers? This question is explored in the context of the Australian Commonwealth which has recently codified a set of public service values in legislation and where agencies are being asked to report on the extent to which they require contractors to comply with public service values. Practice is evolving, with most emphasis on values relating to direct service to the public. Public service values dealing with internal organization and employment conditions, including the merit principle, are less likely to be extended to private contractors. - Reproduced.
Keywords: Outsourcing - Australia; Public administration - Australia; Public administration